2001
DOI: 10.1046/j.1365-2567.2001.01244.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6 regulates the phenotype of the immune response to a tuberculosis subunit vaccine

Abstract: Summary We investigated the role of interleukin‐6 (IL‐6) in the development of the immune response to a subunit vaccine against tuberculosis consisting of the culture filtrate proteins of Mycobacterium tuberculosis emulsified in the adjuvant dimethyldioctadecylammonium bromide (DDA). C57Bl/6 mice immunized with this vaccine developed a strong T helper 1 (Th1) response characterized by an increased production of interferon‐γ (IFN‐γ) secreted by CD4+ T cells. Neutralization of IL‐6 during in vivo priming resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
0
17
0
1
Order By: Relevance
“…Previous studies have shown that NK cells enhance IL-6 production, by MFs and DCs, during early immune responses (45,46). Other studies concentrating on M. tuberculosis have shown that IL-6 is required for early IFN-g production in the lungs of mice infected with M. tuberculosis, and that IL-6 participates in the induction of protective T H 1 T cell responses during vaccination (47)(48)(49). Interestingly, several recent studies have focused on the role of NK cells in IL-22 production (37).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that NK cells enhance IL-6 production, by MFs and DCs, during early immune responses (45,46). Other studies concentrating on M. tuberculosis have shown that IL-6 is required for early IFN-g production in the lungs of mice infected with M. tuberculosis, and that IL-6 participates in the induction of protective T H 1 T cell responses during vaccination (47)(48)(49). Interestingly, several recent studies have focused on the role of NK cells in IL-22 production (37).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the lack of IL-6 neither affected the induction of INPG nor triggered a massive pattern. This cytokine is associated with stimulation of Th1 immunity at the beginning of infection, but does not affect the bacillary load as much as other Th1-related cytokines [42]. Interestingly, the presence or absence of CD8 þ cells, which may contribute to cytotoxicity in M. tuberculosis infection and thus be a key cell population in the induction of necrosis [20], was not significant either for the development of INPG.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, IL-6, which is largely produced by DC in the lymph node has been demonstrated to impact the activation, expansion, survival, and polarization of T cells during an immune response [70]. In various immunization settings, IL-6 signaling is required for optimal T cell priming, the induction of a productive IFN-γ response, protection of T cells from the suppressive activities of Treg, and the acquisition of the ability to provide help to B cells [7173]. In addition to driving the development of CD8 + lymphocyte effector functions, IL-6 has also been described as promoting T cell proliferation following T cell receptor stimulation [5,52].…”
Section: The Fairer Face Of Il-6 In Adaptive Immunitymentioning
confidence: 99%